Pemilihan Umum Indonesia antara Demokrasi Pancasila dan Demokrasi Liberal - Wikrama, Anak Agung Ngurah Agung Wira Bima (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
General election is a tools or facility in implementing democracy which is carried out directly, publicly, freely, confidentially, honestly and fairly. This is in accordance with the principle of democracy, namely from the people, by the people, and for the people as mandated by Article 1 paragraph 2 of the 1945 Constitution. The election is believed to be only as one instrument to encourage the democratic process. Because the increase of mature democracy will reduce injustice and make people's lives more secure in their freedom and encourage the creation more a fair. However, democracy which is carried out through general election in Indonesia now adays is not democracy and the general which is election very suitable for Indonesia. Indonesia has a democratic style mechanism and only exists in Indonesia. Indonesian democracy has been very clearly stated in the 4th principle of Pancasila, which is popularly led by wisdom in deliberation/representation. For this reason, awareness is needed by state leaders and elected board members to be able to understand and explore the values and spirits of Indonesians style democracy. So that Indonesians democracy is getting closer to the spirit and body of Indonesias people.